Social and psychological portrait of the KGB agent - Burinskaitė, Kristina (Genocidas ir rezistencija, 2021)
After 1953, the KGB faced new challenges. With the Soviet system gradually opening, ever more intense relations with the West in the fields of science, culture, industry and tourism were established, which was a certain challenge in protecting strategically important information and ensuring control of the territory. However, it was no longer possible to break civil resistance and the fight of ideas by means of brutal measures alone. Secret collaborators became an ever more important instrument in implementing the KGB tasks. The agent’s environment and in what way he could be of use to the KGB created the greatest value for the agent. Hence, not only professional experience and knowledge but also personal qualities became important. It was not only collection of information that prevailed during the fight against partisans but also the dissemination of certain ideas or rumours, observance and analysis of moods and principles of certain groups of society (the youth, the intelligentsia, representatives of culture, education and clergy), as well as performance of other tasks became of greatest importance in the agents’ work. Hence, the most significant feature in recruiting an individual became his age, education, duties and responsibilities, the social medium in which he worked and lived. The following groups of society are most often referred to in the KGB reports, which determined their choice: the cultural and academic, technical intelligentsia, (teachers, lecturers, physicians, artists, engineers, specialists), political prisoners (deportees), the clergy, the youth, workers (workers and collective farmers). Agents’ education and social situation, perhaps their age to a lesser degree, were determined, speaking in the KGB terms, by the operational situation of a city (region): the geographical location of the territory (e.g., the border), the city of Kaunas as the temporary capital of the interwar period, where there was a great concentration of the intelligentsia, young people, political prisoners and deportees who came back from places of imprisonment, objects of industry, science, education, culture located in other cities, certain social groups, such as the former political prisoners, deportees who maintained contacts with people living abroad and, of course, the factor of the clergy was of great significance. Though it was sought to have as many agents as possible among the young people, political prisoners and the clergy, the KGB reports show that the KGB efforts gave no desired results. The level of education and the social basis of the agency was an integral part of the portrait of the KGB agent. On the basis of the available information about the psychological characteristic of the KGB agents, it is difficult to draw conclusions about the agent’s portrait. However, the specificity of the agent’s activity that included concealing everything from the family, the surrounding people, specific tasks, how to collect and obtain certain information, approaching certain persons – required certain skills such as communicability, but, on the other hand, certain reticence, as well as flexibility and composure. However, the most valuable quality of the agent was the ability to come close to the people and information that were of use to the KGB.